2015
DOI: 10.1123/jtpe.2013-0054
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Technopedagogical Content Knowledge Competencies of Preservice Physical Education Teachers: A Turkish Sample

Abstract: This study examined preservice physical education teachers’ (PPETs’) technopedagogical content knowledge (TPCK) competencies. The participants were 1028 PPETs from 26 major universities representing all seven geographical regions of Turkey. The Technological Pedagogical Content Knowledge Deep- Scale developed by Kabakci Yurdakul et al. (2012) was used to measure TPCK competencies of PPETs. Descriptive statistics, an independent samples t test, and multivariate analysis of variance were used to analyze the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
11

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
1
12
1
11
Order By: Relevance
“…It has been found that substantial intensification of educational process served as significant factor of students' everyday motor activity weakening [5,17,21]. One more important factor of negative influence on students' health is their excessive involvement in computer games and internet [3,20,22]. Deficit of students' everyday motor activity results in emersion of different diseases, excessive increase of body mass and obesity [6,25,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that substantial intensification of educational process served as significant factor of students' everyday motor activity weakening [5,17,21]. One more important factor of negative influence on students' health is their excessive involvement in computer games and internet [3,20,22]. Deficit of students' everyday motor activity results in emersion of different diseases, excessive increase of body mass and obesity [6,25,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that physical culture teachers shall have certain competences. It was found that application of information-communication technologies is an important factor, which influences on teachers' competences in Turkey [20].…”
mentioning
confidence: 99%
“…In this study, environmental factors become the biggest challenge of using technology in Physical Education learning. The key to technology integration in the teaching and learning process of Physical Education is the availability of supporting facilities and infrastructure, such as the availability of the internet and other multimedia equipment [11]. Ease of access through the internet network, the availability of computer labs, projectors, digital cameras and multimedia such as audiovisuals that attract students also to increase student motivation when the learning process takes place [12].…”
Section: Methodsmentioning
confidence: 99%